On the 150th Anniversary of the Universal Postal Union: Revisiting Ottoman Empire’s Overlooked Position in Global Postal History - Yaman, Mehmet Şükrü (Fatih Sultan Mehmet Vakıf Üniversitesi, 2025)
On 9 October 2024, the Universal Postal Union (UPU), recognized as the world’s second-oldest intergovernmental organization, celebrated its 150th anniversary. Its history is rich, multilayered, and marked by unique milestones. As a founding member, the Ottoman Empire occupied a central position in this historical process, playing a decisive role both in the organization of postal services and in shaping humanity’s shared heritage. The bilateral relations between the Ottoman Empire and the UPU, which began with the Bern Congress in 1874 and continued until the proclamation of the Republic, encompassed highly significant phases that have often been overlooked in the literature, with insufficient systematic scholarly attention devoted to them. The scope of this article is limited to an analysis, taking into account the historical significance of postal services, of Western approaches shaped by the attitudes faced and postal realities experienced by the Ottoman Empire at the Bern Congress. Given the international character of the Bern Congress, the study aims to provide a comprehensive background demonstrating how, and to what extent, the salient aspects of the Ottoman Empire’s engagement within the UPU were addressed in external scholarship.

9 Ekim 2024 tarihinde 150. kuruluş yıl dönümünü idrak eden ve dünyanın en eski ikinci hükûmetler arası kuruluşu olarak bilinen Evrensel Posta Birliği’nin tarihi; zengin, çok katmanlı ve eşsiz dönüm noktalarıyla örülü bir geçmişe sahiptir. Osmanlı Devleti, kurucu üye sıfatıyla, bu tarihî sürecin merkezinde yer almış; posta hizmetlerinin örgütlenmesinde ve insanlığın ortak mirasının şekillenişinde de kilit bir aktör olarak belirleyici rol oynamıştır. 1874 yılında Bern Kongresi ile başlayan ve Cumhuriyet’in ilanına kadar uzanan Osmanlı-Evrensel Posta Birliği ilişkileri, son derece önemli aşamalar barındırmakla birlikte, literatürde çoğu kez göz ardı edilmiş, üzerine sistemli biçimde eğilme ihtiyacı yeterince hissedilmemiş bir alandır. Bu makalenin kapsamı, posta hizmetlerinin tarihsel önemini göz önünde bulundurarak, özellikle Osmanlı Devleti’nin Bern Kongresi’nde maruz kaldığı tutum ve tecrübe ettiği posta gerçekliğinin şekillendirdiği Batılı yaklaşımları tahlil ile sınırlıdır. İkili ilişkilerin başlangıcı olan Bern Kongresi, uluslararası nitelik arz ettiğinden, çalışmanın amacı Osmanlı Devleti’nin Evrensel Posta Birliği bağlamında dikkat çektiği hususların dış literatürde ne şekilde ve hangi ölçüde ele alındığını kapsamlı bir arka planla ortaya koymaktır.
UPU’nun 150. Yılında Osmanlı Devleti’nin Küresel Posta Tarihinde Gözden Kaçırılmış Konumuna Yeni Bir Bakış
Keywords: Ottoman Empire; Universal Postal Union; Literature; Foreign Posts; Osmanlı Devleti; Evrensel Posta Birliği; Literatür; Yabancı Postalar